RETELLING STORIES THROUGH PICTURE SERIES TO IMPROVE STUDENTS SPEAKING SKILL - Haryanto, Haryanto; Melinda, Sindi (Center of Language and Cultural Studies, 2022)
Speaking is an effective language talent in verbal exchange that is incorporated collectively with the opposite language competencies consisting of listening, writing, and analyzing despite the grammatical, pronunciation, and vocabulary. This article aims to explain the concept of speaking skills, the implementation of picture series to retelling stories for speaking skills, and the advantages and disadvantages of the retelling story technique. The method of collecting data is through library research and documentation. The data were collected from books and manuscripts. The analysis of data used qualitative data analysis using Miles and Huberman's data analysis process by organizing the information, description, and interpretation. The results of this study show that retelling stories are useful for improving students' ability to speak English by using pictures to improve students' speaking skills.